(3LOGhd QSe GdefMQaGJ YdiGdMjWGfs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s; (3aJM Gddg Hf YeQ GdeGQOjfjs
(3ChdgG (B:s
(3HYO GdOjHGLI bO MSHJ gPg GdLOGhd ai QSe GdefMQaGJ Ydi GdMjWGf HWQjb Sgd MSf CSHb Edjg s
(3BNQgG (B:s
(3LOhd s
(3jJdhgG NeSg LOGhd eJYdbI HGdHQhL agi ef HQL GdYbQH Edi HQL GdMhJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B167 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B28 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B151) s
Keywords: (3Gdadcs